(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
Handling of a medico legal case is not an easy job especially while a doctor is working in an Emergency ward where generally patients are brought in a critical condition needing immediate medical intervention. Same problem may also happen while treating such a case in the wards due to multiple reasons. Doctors may have to work under political pressure and frequent police interventions and most uncomfortably they may receive threats from gonads. To combat this, the present paper discusses some example of medico legal cases and the existing related legal provisions in India.